The Effect of Entrepreneurial Competency on The Performance of Culinary SMES in Banjarbaru, South Kalimantan - Purnamasari, Ni Made Windy Widyastuti; Achmad, Burhanuddin Umar; Jahroh, Siti (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
The income of Micro and Small Culinary Businesses in Banjarbaru in 2015-2019 has increased. Business development can be influenced by entrepreneurial competence and external factors. The purpose of this study was to analyze the effect of individual characteristics and psychological characteristics on entrepreneurial competence, the influence of entrepreneurial competence and external factors on business performance, and the influence of external factors on entrepreneurial competence. This research was conducted using a survey technique. The data analysis tool used SEM. The sample in this study was in the amount of 210. The method of data collection was done by direct interviews and google form through whatssapp respondents. The results of the study showed that entrepreneurs who were tenacious and had high motivation were going to have high entrepreneurial competence. Entrepreneurs having high technical ability had high business performance. Entrepreneurs having many social networks had high business performance. The conclusion of this study was that individual characteristics and psychological characteristics had a positive effect on entrepreneurial competence, whereas entrepreneurial competence and external factors had a positive effect on business performance.